Komodifikasi Al-Qur’an dalam Media Digital - Muhamad Yoga Firdaus; Suryana Alfathah; Dadan Rusmana (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
This article discusses commodification related to the Qur’an in digital media. It uses a qualitative method with a sociological approach of consumptive society initiated by Jean Baudrillard. This research argues that the commodification of the Qur’an cannot be separated from the commodification of religion. On the one hand, the commodification of the Quran was quite large when the printing and publishing of the Qur’an began to flourish. However, on the other hand, the commodification of the Qur’an also occurs in the digital space, especially on television media and YouTube channels. This is due to the phenomenon of consumerism experienced that is rapidly experienced by society. As a result, the essence of the Qur’an may be lost the presentation of television programs and YouTube contents about the Qur’an is currently made only to reach the target market. However, there are also many positives pertaining to the presence of such television shows and YouTube contents in society.